The Impact of Time and Temperature of Drying on the Functional Composition of Kencur (Kaempferia galanga) var. Gading Powder - Irvia Resti Puyanda; Henrikus Andries Gibran; Candra Tika Putri Maharani (Agroindustrial Technology Journal, 2025)
Kencur or Kaempferia galanga is a source of bioactive compounds that can be used as a functional food. One of the varieties of K. galanga in Indonesia is K. galanga var. Gading. This cultivar originates from Nogosari, Boyolali, Central Java, an area recognized for its relatively high K. galanga production. Data from the Central Bureau of Statistics (BPS) of Boyolali Regency (2024) show that the productivity of K. galanga in Nogosari District exceeds 8 tons per hectare, making this cultivar one of the promising and widely cultivated varieties in Indonesia.. K. galanga has a short shelf life due to its moisture content; therefore, drying is considered an effective method to reduce its moisture content. This research aimed to determine the effect of drying time and temperature on the quality of K. galanga powder. This research used a factorial design with two factors: drying temperature (50ºC and 60ºC) and drying time (4, 6, 8 hours). K. galanga was washed, sliced, dried, ground, and analyzed for its chemical and microbial properties. The chemical properties included total phenolic content and antioxidant activity, while the microbial property was evaluated based on the total plate count. The The results showed that drying temperature at 60 °C for 6 h provided the highest total phenolic content (1.45 mg GAE/100 g w.b.), with antioxidant activities respectively from the tests using DPPH 1.47 mg Trolox/100 g w.b. and 7.90 mg Trolox/100 g w.b. by ABTS, which indicated a moderate antioxidant activity. Moreover, that treatment showed a reduction of 15.93% and a total plate count of 120 CFU/g.